2008
DOI: 10.1074/jbc.m801791200
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Regulates Hepatic Peroxisome Proliferator-activated Receptor α Phosphorylation and Activity to Impact Lipid Homeostasis

Abstract: Aldose reductase (AR) is implicated in the development of a number of diabetic complications, but the underlying mechanisms remain to be fully elucidated. We performed this study to determine whether and how AR might influence hepatic peroxisome proliferator-activated receptor ␣ (PPAR␣) activity and lipid metabolism. Our results in mouse hepatocyte AML12 cells show that AR overexpression caused strong suppression of PPAR␣/␦ activity (74%, p < 0.001) together with significant down-regulation of mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
(36 reference statements)
3
32
0
1
Order By: Relevance
“…To examine the potential regulation of PPARα by endogenous cyclin D1, we first utilized the well-differentiated AML12 mouse hepatocyte cell line [29, 30]. Small interfering (si) RNA-mediated knockdown of cyclin D1 efficiently depleted the expression of this protein and inhibited serum-stimulated proliferation of these cells (Figure 2A–2B) [18].…”
Section: Resultsmentioning
confidence: 99%
“…To examine the potential regulation of PPARα by endogenous cyclin D1, we first utilized the well-differentiated AML12 mouse hepatocyte cell line [29, 30]. Small interfering (si) RNA-mediated knockdown of cyclin D1 efficiently depleted the expression of this protein and inhibited serum-stimulated proliferation of these cells (Figure 2A–2B) [18].…”
Section: Resultsmentioning
confidence: 99%
“…AML12 cells were plated on 6-well plates at the cell density of approximately 1.0×10 6 /well. On the next day, cells were transfected with pFLAG-mAR, a plasmid constructed as described previously [15] or pFLAG-CMV2 (Sigma) using Lipofectamine 2000 reagent (Invitrogen) according to the manufacturer’s protocol. 36 hours later, cells were collected for mRNA expression analyses.…”
Section: Methodsmentioning
confidence: 99%
“…RT-PCR was performed to determine the levels of acetyl CoA oxidase ( Aco ), carnitine palmitoyl transferase-1 ( Cpt1 ), apolipoprotein C-III ( ApoC3 ), and apolipoprotein A-V ( ApoA5 ) mRNAs as previously described [17]. The primers used were 5′-CCGCCACCTTCAATCCAGAGTTA-3′ and 5′-TCACAGTTGGGCTGTTGAGAATG-3′ ( Aco ), 5′-GGACGAATCGGAACAGGGATA-3′ and 5′-CCTTGTAATGTGCGAGCTGCA-3′ ( Cpt1 ), 5′-CCTCTTGGCTCTCCTGGCATCT-3′ and 5′-TGCTCCAGTAGCCTTTCAGGG-3′ ( ApoC3 ), 5′-GTGGGAGAAGACAC-CAAG-GCTC-3′ and 5′-GGTCAATGGCCTGAGTAAA-TGC-3′ ( ApoA5 ), 5′-CGAGACCCCACTAA-CATCAAA-3′ and 5′-AGTCTTCTGGGTGGCA-GTGAT-3′ (GAPDH).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that diabetes, type II diabetes mellitus (T2DM) in particular, is often associated with hepatic accumulation of triglycerides in both rodents and humans, which might eventually lead to the development of hepatic steatosis or nonalcoholic fatty liver disease (NAFLD) [1416]. Recently, we demonstrated that deficiency or inhibition of AR caused significant dephosphorylation of hepatic PPAR α , leading to the activation of this transcriptional factor as well significant reduction in serum TG levels in streptozotocin-(STZ-) diabetic mice, an experimental model for type I diabetes mellitus (T1DM) [17]. Because T2DM is clinically much predominant than T1DM, in this current study, we wanted to determine whether AR also affects PPAR α in the liver of T2DM db/db mouse models.…”
Section: Introductionmentioning
confidence: 99%